Viscous solutions for the Hamilton – Jacobi – Bellman equation on time scales - Danilov, V. Ya.; Lavrova, O. E.; Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We introduce the concept of viscous solution for the Bellman equation on time scales and establish сonditions for the existence and uniqueness of this solution.